Visualization Method for Porous Groundwater Seepage Flow Field Based on Particle Flow: Case of Yancheng City in the East Coast of China. (15th November 2022) - He, Liang; Chen, Ling; Chen, Suozhong
Abstract : Porous groundwater seepage flow field reflects the spatiotemporal dynamic characteristics of porous groundwater movement. The geometric point and vector line methods are the traditionally used visualization methods for groundwater seepage flow field; however, they exhibit difficulty in describing the characteristics and attributes of a seepage flow field. Therefore, a new particle flow method in the field of computer graphics is introduced in this study to visualize seepage flow field, including the storage conditions, transport mechanism, and seepage field properties of porous groundwater. This visualization method is discussed from four aspects: the generation of seed points, the life cycle of particles, the movement velocity of particles, and the formation of particle trajectory and smooth processing. The seepage field of confined aquifer III groundwater expressed via particle flow and the contour of critical groundwater level are superimposed and analyzed in Yancheng City in the east coast of China. Results show that particle flow can be effectively applied to the visualization of groundwater seepage flow field and provide spatial auxiliary decision-making support for the sustainable exploitation of groundwater and the formulation of geological environment protection measures.